Qiyam al-Da’wah Fi Syi’ri “Man ‘Arafa” Li Hamzah Fansu>ri> - Sulfikar; Fitriani, Laily; Al-Anshory, Abdul Muntaqim (Jurusan Pendidikan Bahasa Arab, 2024)
Poetry is a concrete form of literary output to express human thoughts and feelings and is used as a medium for preaching in the process of spreading Islam. This study aims to determine the meaning contained in the poem